The Application of Problem Possing Learning Model to Increase Activity and Mathematics Learning Outcomes - Fauzi Martha Lisdyadana; Fury Styo Siskawati; Tri Novita Irawati (Universitas Islam Jember, 2021)
This study aims to improve student activity and learning outcomes through a problem possing learning model. This type of research is classroom action research (CAR). The subjects of this study were students of class VIII SMP An Nisa 'Gumukmas. The data collection method used is the method of testing, observation, interviews and documentation. This research was conducted in two cycles. Based on the results of the research conducted, the percentage of activity in the first cycle was 62.9% and in the second cycle it reached 81.5%, it appears that there is an increase. Then for the percentage of completeness of learning outcomes in cycle I reached 55.6% and in cycle II reached 92%, it appears that there is an increase. Based on the results obtained, it can be concluded that the application of the problem possing learning model can improve student activity and learning outcomes. Keywords: problem possing, learning activity, learning outcomes.